Initial growth of coffee (Coffea arabica L. var) castillo in the coffee zone of Nariño - Criollo, Hernando; Muñoz, Johanna; Checa, Jorge; Noguera, Wilmer (Revista de Ciencias Agrícolas, 2019)
The importance of coffee cultivation in Nariño is reflected in the fact that 64% of its municipalities grow coffee. The ruggedness of its Andean topography provides great diversity in terms of climatic conditions, which, in one way or another, affect the behavior of coffee in all its physiological processes. Therefore, this study sought to identify the variation in the growth processes and production processes in the different coffee areas of this department, including the coffee-growing municipalities Sandoná, Consacá, La Florida and La Unión in the Department of Nariño, using experimental lots located at different altitude ranges (B <1600msnm; M between 1600 and 1800msnm and A >1800msnm). The statistical design used for each municipality was Random Complete Blocks with three treatments and sixteen repetitions. The recorded climatic variables included photosynthetically active radiation, ambient temperature, precipitation and relative humidity, and the evaluated physiological variables were plant height, number of leaves, basal stem diameter, number of primary branches, number of secondary branches, length of primary branches, number of knots per branch and leaf area index. The variable plant height was statistically higher in the upper zone (A) in the municipalities La Florida (79.95 cm) and Consacá (64.31cm); in La Florida, the number of branches and the LAI were higher in the upper zone plants, while the diameter of the stems was higher in the middle zone. In the other municipalities, these variables were not affected by the altitude.